2000
DOI: 10.1046/j.1523-1755.2000.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter trial of mizoribine compared with placebo in children with frequently relapsing nephrotic syndrome

Abstract: Results. The primary analysis was conducted on 99 mizori-A multicenter trial of mizoribine compared with placebo in bine-and 98 placebo-treated patients. The relapse rate was children with frequently relapsing nephrotic syndrome.lower in the mizoribine group than in the placebo group (0.0055 Background. The use of corticosteroids or cytotoxic/immuvs. 0.0067; ratio 0.81, 95% CI, 0.61 to 1.05, P ϭ 0.12). The nosuppressive agents such as cyclophosphamide, chlorambucil, hazard ratio of the cumulative remission rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
97
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 24 publications
(2 reference statements)
1
97
0
1
Order By: Relevance
“…To note, however, four of five children who were excluded from analysis due to relapse during tapering were steroid dependent; inclusion of these children would have strengthened the association between steroid dependency and risk. In six patients (three each in group A and B), mizoribine, an agent in the same antimetabolite class as mycophenolate mofetil whose efficacy is mild and limited to patients aged #10 years (21), was administered during follow-up to prevent regression to FRNS (data not shown). On inclusion in Poisson analyses, administration of mizoribine was positively associated with relapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To note, however, four of five children who were excluded from analysis due to relapse during tapering were steroid dependent; inclusion of these children would have strengthened the association between steroid dependency and risk. In six patients (three each in group A and B), mizoribine, an agent in the same antimetabolite class as mycophenolate mofetil whose efficacy is mild and limited to patients aged #10 years (21), was administered during follow-up to prevent regression to FRNS (data not shown). On inclusion in Poisson analyses, administration of mizoribine was positively associated with relapse.…”
Section: Discussionmentioning
confidence: 99%
“…First, although protocols for the administration of immunosuppressants and prednisolone after treatment with cyclosporine were provided, treatment was at the discretion of the physician in charge. Immunosuppressants were occasionally started before criteria for the diagnosis of FRNS or SDNS had been met, and mizoribine to prevent relapse was sometimes started very early, even before the first relapse, owing to its low incidence of adverse events (21). Second, several data points were missing, including some measurements of height and serum creatinine, particularly among stable children.…”
Section: Discussionmentioning
confidence: 99%
“…1,15,16) However, the relationship between the therapeutic effect and serum concentration of mizoribine is unclear, and the optimal dose of the drug for autoimmune diseases as well as organ transplantation is still unkown. 15) Because the serum mizoribine concentration can be easily measured by an HPLC method, monitoring the serum mizoribine concentration in the patients may be useful to assess the relationship between the drug exposure (AUC and/or C max ) and response.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary data from a series of pediatric (1)(2)(3)(4)(5)(6)(7)(8) and adult (9 -11) studies suggest that mycophenolate mofetil (MMF) may represent a less toxic alternative for patients with FRNS. Other recent studies have reported that mizoribine (12)(13)(14)(15)(16)(17) or levamisole (18) also may be options to consider in such patients.…”
mentioning
confidence: 99%